Screen Production Research Creative Practice as a Mode of Enquiry (Springer International Publishing, 2018)
Aimed at students and educators across all levels of Higher Education, this agenda-setting book defines what screen production research is and looks like-and by doing so celebrates creative practice as an important pursuit in the contemporary academic landscape. Drawing on the work of international experts as well as case studies from a range of forms and genres-including screenwriting, fiction filmmaking, documentary production and mobile media practice-the book is an essential guide for those interested in the rich relationship between theory and practice. It provides theories, models, tools and best practice examples that students and researchers can follow and expand upon in their own screen production projects.